Accessing diagnosis and treatment: The experience of cancer as wrangling with the system - Dew K; Chamberlain K; Egan R; Broom A; Dennett E; Cunningham C (Elsevier B.V., 2024)
Long term cancer survival is increasingly prevalent, and the consequences are of sociological and clinical interest. In this paper we deploy the concept of wrangling to emphasise the everyday tussle of survivorship and processes of navigating pathways through what can be an unwelcoming environment. From 2020 to 2022 81 interviews were conducted with people, Māori and non-Māori, throughout Aotearoa New Zealand identified as exceptional cancer survivors, living with a diagnosis of cancer from four to 37 years. Categories of wrangling discussed by participants included wrangling with the public drug-buying agency in Aotearoa New Zealand, wrangling between private and public healthcare systems, subaltern wrangling and wrangling across regions. Wrangling could be driven by the person with the cancer diagnosis, undertaken on behalf of that person by others including family and health professionals, and undertaken by the community. We argue that for most people with long-term cancer survival wrangling is a social practice, but the capacity to succeed in that practice is dependent on a range of factors, including levels of economic, cultural, and social capital. The concept of wrangling provides a contrast to an overemphasis in the survivorship literature on cancer as an individual experience; one largely disconnected from the art and practice of managing (often unwieldy and flawed) systems of care.
Keywords: Cancer survivorship; Wrangling; Cultural health capital; Aotearoa New Zealand